2021
DOI: 10.3390/geriatrics6030066
|View full text |Cite
|
Sign up to set email alerts
|

Proof of Concept of Novel Visuo-Spatial-Motor Fall Prevention Training for Old People

Abstract: Falls in the geriatric population are one of the most important causes of disabilities in this age group. Its consequences impose a great deal of economic burden on health and insurance systems. This study was conducted by a multidisciplinary team with the aim of evaluating the effect of visuo-spatial-motor training for the prevention of falls in older adults. The subjects consisted of 31 volunteers aged 60 to 92 years who were studied in three groups: (1) A group under standard physical training, (2) a group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 236 publications
0
1
0
Order By: Relevance
“…Additionally, Scanlan et al (2014) state that cognitive abilities, especially response time and decision-making, have been consistently identified as key factors in reactive agility performance in adolescent basketball players [17]. These findings are further supported by Zwierko et al (2022), who found that the complex reaction time, which belongs to perceptual capacities, significantly contributes to reactive agility in young male volleyball players [24,25]. Despite the huge amount of studies declaring cognitive abilities as an important factor influencing reactive agility performance, our research did not confirm these findings.…”
Section: Correlates Of Cognitive Abilities and Agilitymentioning
confidence: 77%
“…Additionally, Scanlan et al (2014) state that cognitive abilities, especially response time and decision-making, have been consistently identified as key factors in reactive agility performance in adolescent basketball players [17]. These findings are further supported by Zwierko et al (2022), who found that the complex reaction time, which belongs to perceptual capacities, significantly contributes to reactive agility in young male volleyball players [24,25]. Despite the huge amount of studies declaring cognitive abilities as an important factor influencing reactive agility performance, our research did not confirm these findings.…”
Section: Correlates Of Cognitive Abilities and Agilitymentioning
confidence: 77%